Light-Driven Liquid Crystal Circular Dammann Grating Fabricated by a Micro-Patterned Liquid Crystal Polymer Phase Mask - Wang, Xiaoqian; Wu, Saibo; Yang, Weiqiang; Yuan, Conglong; Li, Xiao; Liu, Zhen; Tseng, Manchun; Chigrinov, Vladimir; Kwok, Hoising; Shen, Dong; Zheng, Zhigang (Polymers, 2017)
As one of the diffractive optical elements, circular Dammann grating has shown its excellent versatility in practical applications. The electrically switchable Dammann grating has been extensively investigated; however, the research on the optically tunable circular Dammann grating has received less attention and reports on this subject have been insufficient in the past decade. In this paper, three-order and eight-order binary-phase liquid crystal circular Dammann gratings with two mutually orthogonal photo-induced alignments in every two adjacent alignment domains, fabricated by a micro-patterned liquid crystal polymer phase mask, are proposed to generate annular uniform-intensity patterns in the far field. A simple maskless optical tuning of an eight-order liquid crystal circular Dammann grating is demonstrated by controlling the polarization of an ultraviolet light as well as the energy dose. The proposed liquid crystal circular Dammann gratings with high efficiencies and desirable uniformities exhibit outstanding optical as well as electrical tunabilities, enabling the widespread prospective applications in adaptive photonic chips stimulated flexibly by only light or by the combination of light and electric field.